Studi Kebijakan dalam Pengadaan Dassault Rafale sebagai Alutsista Indonesia - Novitasari Wahyu Hastami; Ali Zainal Abidin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to determine the factors that influence the procurement of Dassault Rafale from France. This research is a qualitative descriptive study using the literature review method. Data collection was sourced from literature such as books, local and international journal articles, a collection of press releases and actual news, as well as official websites of agencies related to this research. This study discusses the implementation of the Dassault Rafale procurement policy in Indonesia when some aspects do not recommend it. As a result, there were political and economic considerations that culminated in the decision to bring in the Dassault Rafale even though there are more sophisticated and cheaper fighter jets because Indonesia needs to be careful in deciding a policy, especially in considering the negative impact of politics. and economic aspects. In the procurement of the Dassault Rafale, the policies adopted were heavily influenced by international politics, especially due to the existence of the CAATSA Law. Indonesia's free and active foreign policy still needs to be implemented, but the government also needs to pay attention to regional geostrategy and domestic economic conditions in the future in the procurement of defense equipment